Volume 1: Regulations, Codes, and Standards; Current Issues; Materials; Corrosion and Integrity 1996
DOI: 10.1115/ipc1996-1860
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of High-pH and Near-Neutral-pH SCC of Underground Pipelines

Abstract: This paper provides an overview of mechanisms for high-pH and near-neutral-pH stress corrosion cracking of underground pipelines. Characteristics and historical information on both forms of cracking are discussed. This information is then used to support proposed mechanisms for crack initiation and growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Their conclusion was that higher crack growth rates were observed at lower fiequencies for a given LX because of a longer exposure time to the entironment for each cycle. Parkins et al (1994) found that crack g r o~~ rates tvere not a function of frequency for non-classical SCC, which also agrees with Beavers et al (1998). Parkins et al (1994) also found that the average crack velocity and the density of cracks increased with maximum stress.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Their conclusion was that higher crack growth rates were observed at lower fiequencies for a given LX because of a longer exposure time to the entironment for each cycle. Parkins et al (1994) found that crack g r o~~ rates tvere not a function of frequency for non-classical SCC, which also agrees with Beavers et al (1998). Parkins et al (1994) also found that the average crack velocity and the density of cracks increased with maximum stress.…”
Section: Resultssupporting
confidence: 71%
“…The high lZ2 value means that the voltage range, -10 mV to +10 mV about Eco,: was the proper range since too large of a range will deviate from being linear and make rhe approximation incorrect. The existence of only an active behaviour in the PD scans as opposed to a active/passive behaviour is consistent with other researchers (Liu et ai., 1993 andBeavers et al, 1998). Liu et al tested X-80 linepipe in bicarbonate solutions varying in concentration from 0.005 M to 1 M as welI as an NS4 solution.…”
Section: X-70 Linepipe Steelmentioning
confidence: 99%
“…Earlier studies have shown that it is very difficult to initiate or propagate colonies of near-neutral pH cracks in the absence of stress concentrators or fatigue loading in the laboratory [15,16]. However, recent studies have shown that dynamic loading is effective in accelerating crack growth, but is not essential in the formation and growth of cracks, as cracks are found to develop on the surface of the SCC samples after prolonged constant-load testing [3,4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery of SCC on the exterior surface of a buried high pressure natural gas transmission pipeline in 1965 (Leis & Eiber, 1997), SCC has continued to make a significant contribution to the number of leaks and ruptures in pipelines. Two forms of SCC can exist on buried steel pipelines (Beavers & Harle, 2001). The first discovered form of SCC propagates intergranularly and is associated with a concentrated alkaline electrolyte in contact with the steel surface, commonly called as high pH-SCC or classical SCC.…”
Section: Introductionmentioning
confidence: 99%
“…A corrosion potential between 760 to 790 mV, Cu/CuSO 4 was observed, and wide cracks with evidence of corrosion. A comparative table of both SCC types was given elsewhere (Beavers & Harle, 2001). …”
Section: Introductionmentioning
confidence: 99%